Dietary Arginine Regulates Severity of Experimental Colitis and Affects the Colonic Microbiome - Singh, Kshipra; Gobert, Alain P.; Coburn, Lori A.; Barry, Daniel P.; Allaman, Margaret; Asim, Mohammad; Luis, Paula B.; Schneider, Claus; Milne, Ginger L.; Boone, Helen H.; Shilts, Meghan H.; Washington, M. Kay; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
There is great interest in safe and effective alternative therapies that could benefit patients with inflammatory bowel diseases (IBD). L-arginine (Arg) is a semi-essential amino acid with a variety of physiological effects. In this context, our aim was to investigate the role of dietary Arg in experimental colitis. We used two models of colitis in C57BL/6 mice, the dextran sulfate sodium (DSS) model of injury and repair, and Citrobacter rodentium infection. Animals were given diets containing 1) no Arg (Arg0), 6.4 g/kg (ArgNL), or 24.6 g/kg Arg (ArgHIGH); or 2) the amino acids downstream of Arg: 28 g/kg L-ornithine (OrnHIGH) or 72 g/kg L-proline (ProHIGH). Mice with DSS colitis receiving the ArgHIGH diet had increased levels of Arg, Orn, and Pro in the colon and improved body weight loss, colon length shortening, and histological injury compared to ArgNL and Arg0 diets. Histology was improved in the ArgNL versus Arg0 group. OrnHIGH or ProHIGH diets did not provide protection. Reduction in colitis with ArgHIGH diet also occurred in C. rodentium-infected mice. Diversity of the intestinal microbiota was significantly enhanced in mice on the ArgHIGH diet compared to the ArgNL or Arg0 diets, with increased abundance of Bacteroidetes and decreased Verrucomicrobia. In conclusion, dietary supplementation of Arg is protective in colitis models. This may occur by restoring overall microbial diversity and Bacteroidetes prevalence. Our data provide a rationale for Arg as an adjunctive therapy in IBD.